Lightning Potential Forecast Evaluation and Its Correlation with Thermodynamic Indices - Flora Gofa; Dimitra Boucouvala; Ioannis Samos; Petroula Louka (Environmental Sciences Proceedings, 2023)
Lightning potential index (LPI) is a measure of the potential for charge generation and separation that leads to lightning flashes in convective thunderstorms and can be forecasted from NWP models. While the connection between cloud microphysics and lightning seems apparent, the common indices used for forecasting thunderstorms and the potential for lightning usually rely on stability and thermodynamic indices. Herein, an effort is made to correlate LPI high-resolution forecasts with observed lightning from local networks. In this way, the usefulness of the LPI for predicting lightning for the Greek territory and its significance as a tool for improving the weather forecasting of convective storms and heavy rainfall are demonstrated. In addition, a statistical evaluation of precipitation and lightning forecasts with novel spatial methods on selected intense precipitation events is performed by comparing them with gridded observation datasets, and the correlation of the results is determined.